Evaluating the readiness of nurses for massive open online courses (MOOCs) in continuing nursing education - Aung, Khin Thandar; Abdul Razak, Rafiza; Mohamad Nazry, Nor Nazrina; Mohd Ali, Noor Azizah (Journal of Contemporary Social Science and Education Studies, 2023)
E-learning is crucial for continuing education and enables flexibility, innovation, and professional advancement. Massive open online courses (MOOCs) provide quality education and support continuing education for diverse populations. Assessing participants' readiness before launching a MOOC course ensures its success. MOOC course preparation, especially in continuing nursing education, is currently understudied. Therefore, this study examined nurses' readiness for MOOC courses for continuing education. A descriptive, cross-sectional study using the convenience sampling method was conducted among registered nurses at SASMEC@IIUM in Kuantan, Malaysia through online survey with google form. The survey consisted of three parts: Part A: demographic characteristics; Part B: MOOC preparedness level in technology access, online skills and relationship, willingness to learn, learning skills in online audio/video, and ability in internet conversation; and Part C: types of preference in MOOC course format. SPSS 22.0 was used for the descriptive analysis. According to results, participants were ready to learn the MOOC course based on technology access, online skills, relationships, and internet conversation. However, it was necessary to plan for online audio and video to support their motivation and learning skills as they had lower average scores (3.8 and 3.9 respectively) than technology access, online skills, relationship and ability in internet discussion (4.4,4.2, and 4.1, respectively on a 5-point Likert scale). This study provided valuable information to the MOOC team and highlighted the need to motivate participants while delivering the MOOC course.